Phytochemical study of cosmetics for hair coloring - Pietrzyk, D; Paradowska, K; Wawer, I; Diakonova, Ia (Annals of Mechnikov’s Institute, 2020)
Introduction Henna-based cosmetic products are becoming increasingly popular. They can be used during pregnancy, lactation as well as for temporary children’s tattoo. The aim of this work is to develop quality control methods, allowing determining the naturalness of the composition of hair coloring cosmetic products, as well as the presence of lawsone and its quantitative content. Material & methods The researched objects were eight hair coloring cosmetic products. The spectrophotometer UV-vis Evolution 60S was used in our phytochemical studies. The quantitative content of chlorophyll a and b was determined in methanolic extracts by spectrophotometric method, using the methodology proposed by K. Miazek. By using well-known methods, methanolic and aqueous extracts were obtained from the studied objects. The extracts, then, were purified to obtain dry residues containing lawsone. Hair color pastes were obtained according to the instructions on the packages of researched products, and finally chloroform extracts were obtained from these pastes.Quantitative content of lawsone in methanolic and aqueous extracts and dry residues after cleaning of the extracts were determined by the spectrophotometric method. The wavelengths at which the solution of lawsone gives absorption maxima were determined experimentally on the basis of the spectra of the standard sample of lawsone dissolved in methanol (methanolic extracts) and in water with the addition of aqueous NaHCO3 (aqueous extracts).The quantitative content of polyphenolic compounds in methanolic and aqueous extracts of the researched objects in terms of gallic acid was performed by the spectrophotometric method at the wavelength of 765 nm using the technique of Folin - Ciocalteau. The gallic acid (by virtue of absorbance dependence on concentration) was used as a standard sample to construct the calibration graph. Results & discussion The total content of chlorophyll in the samples was determined by spectrophotometric method. The resulting calculated ratio of chlorophyll a to chlorophyll b for researched objects 1-8 was 1 - 2.35, 2 – 2.0, 3 – 4.05, 4 – 3.76, 5 – 4.29, 6 – 0.28, 7 – 0.21, 8– 0.19, respectively. However, the samples 1-5 contain substances of a plant origin. Quantitative content of lawsone in the methanolic extracts of samples 3, 4, 5 was 3.9, 4.5%, 5.9%, respectively, at the wavelength of 249 nm and 3.7%, 4.3%, 6.7%, respectively, at 275 nm. Quantitative content of lawsone in aqueous extracts (without adding NaHCO3) of samples 3, 4, 5 was 6.5%, 5.2%, 5.8%, respectively, and 9.2%, 8.6%, 7.9%, respectively, for aqueous extracts with the addition of NaHCO3. Quantitative content of lawsone in the dry residues after extraction with methanol and subsequent purification in samples 3, 4, 5 was 3.9%, 1.7%, 3.5%, respectively. Quantitative content of lawsone in the dry residues after water extraction and subsequent treatment in samples did not change. The highest content of polyphenolic compounds (in mg/g) found in the methanolic extracts of samples 8, 5, 4 and 3 was 83.3, 71.1, 65.2 and 59.3, respectively. The lowest content of polyphenolic compounds was found in aqueous extracts with the addition of NaHCO3 solution of researched objects 7 and 2, amounting 6.8 and 13.7, respectively. Conclusions Based on the ratio of chlorophylls a and b in the researched objects, it was concluded that the samples 1-5 contain components of plant origin. Spectra of aqueous extracts of the samples cannot be used for qualitative determination of lawsone, while the spectra of methanolic extracts can be used only as an auxiliary means, because they do not provide a definite answer. The measurement of the concentration of lawsone in the aqueous and methanolic extracts by spectroscopic method does not give plausible results, as these extracts (except lawsone) contain substances that have their own absorption at the same wavelengths as lawsone. This method can be used to quantify lawsone only after purification of the extracts.The results of this phytochemical study of cosmetics for hair coloring can be used to establish quality control methods for this type of products.